Effects of maternal separation on serotonergic systems in the dorsal and median raphe nuclei of adult male Tph2-deficient mice - Lieb, Margaret W. (Behav Brain Res, 2019)
Previous studies have highlighted interactions between serotonergic systems and adverse early life experience as important gene x environment determinants of risk of stress-related psychiatric disorders. Evidence suggests that mice deficient in Tph2, the rate-limiting enzyme for brain serotonin synthesis, display disruptions in behavioral phenotypes relevant to stress-related psychiatric disorders. The aim of this study was to determine how maternal separation in wild-type, heterozygous, and Tph2 knockout mice affects mRNA expression of serotonin-related genes. Serotonergic genes studied included Tph2, the high-affinity, low-capacity, sodium-dependent serotonin transporter (Slc6a4), the serotonin type 1a receptor (Htr1a), and the corticosterone-sensitive, low-affinity, high-capacity sodium-independent serotonin transporter, organic cation transporter 3 (Slc22a3). Furthermore, we studied corticotropin-releasing hormone receptors 1 (Crhr1) and 2 (Crhr2), which play important roles in controlling serotonergic neuronal activity. For this study, offspring of Tph2 heterozygous dams were exposed to daily maternal separation for the first two weeks of life. Adult, male wild-type, heterozygous, and homozygous offspring were subsequently used for molecular analysis. Maternal separation differentially altered serotonergic gene expression in a genotype- and topographically-specific manner. For example, maternal separation increased Slc6a4 mRNA expression in the dorsal part of the dorsal raphe nucleus in Tph2 heterozygous mice, but not in wild-type or knockout mice. Overall, these data are consistent with the hypothesis that gene x environment interactions, including serotonergic genes and adverse early life experience, play an important role in vulnerability to stress-related psychiatric disorders.